Public Policy for Food and Nutritional Sovereignty and Security of Cali updated based on the Food System Profile of City of Cali - CGIAR Research Program on Water, Land and Ecosystems (2021)
A WLE/Alliance city food system profile is being used as a tool to influence public discourse, educate university students and strengthen policy in the city of Cali, Colombia.